Two new monoterpenoid indole alkaloids from Tabernaemontana divaricata. Issue 15 (3rd August 2019) - Yuwen, Huansha; Yuan, Yuxi; Hao, Xiaojiang; He, Hongping; Zhang, Yu
Abstract: Two new monoterpenoid indole alkaloids, tabervarines A (1 ) and B (2 ), along with seven known monoterpenoid indole alkaloids, were isolated from the methanol extract of the twigs and leaves of Tabernaemontana divaricata. The structures including the absolute configurations of the new alkaloids were elucidated based on MS, NMR, and ECD calculation. The in vitro cytotoxic activities of the isolated alkaloids against several human cancer cell lines were also evaluated. Abstract :